STRATEGI PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI WILAYAH PESISIR KECAMATAN SUPPA KABUPATEN PINRANG - Damis Damis; Armayani Armayani; Surianti Surianti; Hasrianti Hasrianti; A. Rini Sahni Putri; Muhammad Saenong (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
The purpose of this research is to analyze the development strategy of seaweed cultivation to increase seaweed production in the coastal area of Suppa District, Pinrang Regency. This research was conducted in the coastal area of Supa District, Pinrang Regency from May to December 2021. Data collection methods include observations, interviews and documents. The data analysis used is a SWOT analysis. The results showed that the main factors for developing seaweed cultivation business strategies to increase production in the coastal areas of Suppa District, Pinrang Regency, are a) development of aquaculture, b) providing training in stages, c) providing consultations, d) optimizing existing production capacity, e) Expanding planting areas, f) optimizing production, g) increasing funding, h) expanding and maintaining marketing networks.